Design and development of a new stabilization mechanism for two-wheeled wheelchair - Altalmas, Tareq M.K (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
This research embarks on designing a new mechanism for transforming a four-wheeled wheelchair into a two-wheeled wheelchair. It is known that wheelchair system is a main means of mobility for the disabled and the elderly. A normal four wheels wheelchair has some limitations where the wheelchair user is too depending on the helper, which reduces their mobility if the assistance is not available. The standard wheelchair nowadays only caters for outdoor environment where the space is not a constraint. Therefore, the two-wheeled wheelchair is proposed to encourage independence where many common tasks such as pick and place things can be done independently and is suitable to be used in confined space i.e. home, office or library. The proposed two-wheeled wheelchair was modeled to mimics a double inverted pendulum scenario where Link2 was introduced to cater for the human weight. To increase the confidence level of the modeling stage, a virtual prototype of a two-wheeled wheelchair was developed with a human model. Analysis of the model was conducted and simulated to study the actuators requirement and response performance. The mathematical models were then derived to represent the two-wheeled wheelchair. It was achieved that the equations derived represents the system as a highly nonlinear and unstable system. The complexity of the system was reduced through the linearization of the equations. Both linearized and nonlinear equations of motions were tested with different control strategies, where the LQR was implemented on the linearized model and the fuzzy logic controller was designed to control the nonlinear model of the two-wheeled wheelchair. Upon satisfactory results of analysis on the virtual prototype and mathematical models with controllers, a full hardware prototype was developed. The controllers designed were tested experimentally and it provides promising results where the four-wheeled wheelchair was able to transform into a two-wheeled wheelchair and stabilized at the upright position as required.